Thermal Cycling Behavior of Thin WC-Co Sintered Pellets - Alvarez, Esteban Alejandro; García Fierro, José Luis; Gonzalez Oliver, Carlos Julian R. (Wiley VCH Verlag, 2017)
Fil: Alvarez, Esteban Alejandro. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina